Dynamics of Psychological Reactions at the Start of the Pandemic of COVID-19 - Enikolopov S.N.; Boyko O.M.; Medvedeva T.I.; Vorontsova O.U.; Kazmina O.Yu. (Психолого-педагогические исследования, 2020)
The goal of the work is to study the dynamics of psychological changes unfolding during the COVID-19 pandemic. The paper presents an analysis of the responses to the survey on the Internet, received from 03.22.2020 to 04.04.2020, when the spread of COVID-19 begins in Russia. The study was conducted on the Internet using Google Forms. Links to the survey were posted on social networks. The survey involved 430 people, including 188 people in Moscow, and the answers were divided into 3 groups with respect to the date when they were received: March 23–24 (79 people), March 29–30 (46 people), March 31–April 4 (63 people). The survey included a general block of questions and methods SCL-90-R, COPE, OKM97. Statistical processing was carried out with the SPSS statistical package. The results of the study show an increase in psychopathological symptoms (somatization, phobic symptoms, sleep disturbances), a decrease in the level of constructive thinking and indicators of emotional consciousness, an expansion of ideas about esoteric thinking, naïve optimism, categorical thinking, a turn to religion and a search for existential explanations for what is happening. In the Moscow sample, a V-shaped graphs were noted for the parameters of the level of depression, for the severity of obsessive-compulsive symptoms, for the parameters for “turning to religion”, “esoteric thinking,” along with a constant increase in the level of anxious, phobic symptoms and somatization, which leads to the presence of the negation phase after the phase of shock and before the adoption of a situation. Conclusions: with prolonged situation a further increase in psychopathological symptoms is possible, which can have a wide range of negative consequences.